PENERAPAN SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI MAHASISWA BERPRESTASI MENGGUNAKAN METODE AHP - Titis Handayani (Jurusan Teknologi Informasi Universitas Semarang, 2012)
Decision support systems play a role in helping the university to take appropriate decisions. In this study has made a Decision Support System for Selection of Student Achievement which serves to help the university take the right decision by using the method of Analytical Hierarchy Process (AHP). The main function of this system is to process the data selection of outstanding students college level.